Experimental distinction of the molecularly induced Balmer emission contribution and its application for inferring molecular divertor density with 2D filtered camera measurements during detachment in JET L-mode plasmas. (1st July 2022) - Karhunen, J; Holm, A; Lomanowski, B; Solokha, V; Aleiferis, S; Carvalho, P; Groth, M; Lawson, K D; Meigs, A G; Shaw, A; ,
Abstract: A previously presented model for generating 2D estimates of the divertor plasma conditions at JET from deuterium Balmer line intensity ratios, obtained from tomographic reconstructions of divertor camera images, was amended to consider also the Balmer emission arising from molecular processes. Utilizing the AMJUEL and H2VIBR atomic and molecular databases of EIRENE enabled also inference of the molecular divertor density from the distinguished molecularly induced emission. Analysis of a JET L-mode density scan suggests the molecularly induced emission accounting for up to 60%–70% and 10%–20% of the Balmer D α and D γ intensities, respectively, at the onset of detachment, while electron-ion recombination becomes increasingly dominant with deepening detachment. Similar observations were made by post-processing EDGE2D-EIRENE simulations, which indicated significant roles of molecular D 2 + ions and vibrational excitation of the D2 molecules as precursors for the molecularly induced emission. The experimentally inferred molecular density at the outer strike point was found to increase monotonously with decreasing strike point temperature, reaching approximately 30%–50% of the local electron density at n m o l, o s p = 1–2 × 10 20 m −3 at T e, o s p ≈ 0.7 eV. A further steep increase by a factor of 3–5 was observed with decrease of T e, o s p to 0.5 eV. The observations are in qualitative and reasonable quantitative agreement with EDGE2D-EIRENE predictions of n m o l, o s p within the uncertainties of the experimental data.